ANALISIS PENERAPAN STRATEGI PEMASARAN MELALUI BAURAN PEMASARAN TERHADAP MINAT BELI KONSUMEN PADA PT.NUSANTARA SAKTI PANGKALPINANG - Kamelia; Zamhari; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2019)
The Analytical method used is a descriptive analysis method and a questionnaire that uses multiple linear regression analysis tools, simultaneous significant testing and partial significant testing. Work on the data analysis method using the help of MS.Office Excel 2007 and JAPS 0.9.2.0 Universiteit-van-amsterdam application. The data used are secondary data and this study uses 100 respondents as research samples drawn based on the Slovin formula. The results showed that simultaneous product, price, promotion, and place had a positive effect on consumer buying interest with a value of 80.479> from ftabel of 2.47, while partially a variable that had a significant influence on consumer buying interest was a product variable with the result of t (2,453)> t table (1.66105), price variable with tcount result (5.507)> ttabel (1.66105), and promotion variable with tcount result (5,049)> ttable (1,1,66980), and for promotion variables (2,962)> t table (1.66105) while for the place variable has no influence with the value of t (0.545) <t table (1,1,66980). The conclusion that can be drawn from this research is that PT. Nusantara Sakti Pangkalpinang must continue to continuously pay attention to and improve the 4P marketing mix in carrying out its marketing strategy because it is proven to increase consumer buying interest at PT. Nusantara Sakti Pangkalpinang. For other researchers who want to find out more about the factors that influence consumer buying interest, they can add or expand independent variables in further research.